Sanksi Terhadap Pelaku Tindak Pidana Pencurian (Studi Kasus Pengadilan Negeri Sigli) - Safriadi; Muhammad Iqbal (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to determine the process of settling the perpetrators of theft in the Sigli District Court, and to find out the sanctions imposed on the perpetrators of criminal acts of theft at the Sigli District Court, and to find out the Islamic Law's view of the sanctions for the perpetrators of criminal acts of theft. To collect the data, the writer used the library research method, namely studying the books and documents relevant to the discussion of this thesis, while the field data collection was through field research methods using observation, documentation and interview techniques. The results showed that the process in solving the perpetrator of the crime of theft at the Sigli District Court, namely the stage of examination, evidence and verdict. And in solving the criminal case of theft at the Sigli District Court, there are no obstacles or obstacles in solving it. In the Criminal Code, the criminal act of theft is threatened with five years imprisonment and a fine. Whereas in Islamic law the crime of theft is punishable by cutting off hands if the elements and conditions are met. If the elements are not fulfilled, there is another form of law, namely being punished with ta'zir punishment. Islamic law is more flexible because the mechanism of giving sanctions looks at the background and reasons of the perpetrator and sees the social situation and conditions of the community. This is because Islamic law is more concerned with the aspect of the soul, namely protecting oneself from destruction for the sake of human survival.